DIAGNOSTIC VALUE OF STUDYING THE LEVELS OF PRO- AND ANTI-INFLAMMATORY CYTOKINES OF THE IMMUNE SYSTEM IN PATIENTS WITH BREAST CANCER - L. T. Alimkhodjaeva (ABV-press, 2014)
The diagnostic value of the serum levels of proinflammatory (TNF-α, IL-1β, IL-6, and IFN-γ) and anti-inflammatory (IL-4 and IL-10) cytokines of the immune system was studied in 54 patients with breast cancer (BC). Analysis identified the increased concen- trations of proinflammatory cytokines, such as IL-1β, TNF-α, and IL-6, in the peripheral sera of BC patients.Analysis of anti-inflammatory cytokines in the peripheral sera of patients with BC also revealed a significant increase in the values of IL-4 and IL-10. The findings suggest that there is imbalance between cellular and humoral immunity factors, the study of which will be an important diagnostic criterion for BC.